Recent advances predict a bright future for nebulizers. Issue 2 (9th March 2023) - Troy, Michael; Van Vleet, Joseph; Tashkin, Donald; Barjaktarevic, Igor
Abstract : Purpose of review: With the improvement in device technology and delivery methods of inhaled medications, along with development of novel compounds and recognition of the importance of personalized approach in the management of chronic airway diseases, nebulizers have not only maintained their place in the treatment hierarchy of airway disease but have also proven a vital platform for the development of new classes of drugs. Recent findings: This short review explores recent advances in nebulized drug delivery in chronic obstructive pulmonary disease and other chronic airway diseases, emphasizing the progress in nebulizer technology, physiologic advantages of nebulized drug delivery and the high versatility of currently available and developing nebulizer-delivered pharmacotherapies. Summary: Versatility and efficiency of nebulizers allows for a broad spectrum of existing and novel therapies to be clinically studied, facilitating the progress in phenotype-targeted pharmacotherapies in the management of chronic airway diseases